Pharmacognostical studies on the leaves of Ficus altissima blume - Nagiat T Hwisa, Babu Rao Chandu, Prakash Katakam and Srikanth Nama (Journal of Applied Pharmaceutical Science, 2013)
Ficus altissima Blume belonging to family Moraceae is perennial tree with 20-30 ft tall distributed in the hills of northern India and deccan peninsula, up to an altitude of 100-2000 m. It is commonly known as Council Tree. Leaves and bark are used in skin diseases. The tree is one of the recorded hosts of the Indian lac insect and is a source of red colour. Owing to its unexplored medicinal importance, the macroscopic and the microscopic characters of the leaves were studied which will serve as reference standard in identification of the tree.
Keywords: Ficus altissima, Moraceae, leaves